Novel trimeric human cytomegalovirus glycoprotein B elicits a high-titer neutralizing antibody response. Issue 37 (5th September 2018) - Cui, Xinle; Cao, Zhouhong; Wang, Shuishu; Lee, Ronzo B.; Wang, Xiao; Murata, Haruhiko; Adler, Stuart P.; McVoy, Michael A.; Snapper, Clifford M.
Highlights: There is no prophylactic vaccine for human cytomegalovirus (HCMV) in clinical use. A monomeric recombinant gB demonstrated 50% efficacy in preventing HCMV infection. Native trimeric HCMV gB is the ideal structure for eliciting neutralizing antibody. Recombinant trimeric HCMV gB is efficiently produced in Chinese hamster ovary cells. Trimeric HCMV gB elicits markedly higher titers neutralizing activity against HCMV. Abstract: Human cytomegalovirus (HCMV) is a major cause of disability in congenitally infected infants and in the immunosuppressed. There is currently no licensed prophylactic HCMV vaccine. The HCMV envelope glycoprotein B (gB) is considered a major vaccine target antigen based on its critical role in mediating viral-host cell fusion and thus viral entry. The natural conformation of HCMV gB within the viral envelope is a trimer, but there has been no reported success in producing a recombinant trimeric gB suitable for vaccine use. Phase II clinical trials of a monomeric recombinant gB protein demonstrated 50% efficacy in preventing HCMV infection in seronegative women of reproductive age, and in reducing viremia in solid organ transplantation recipients. We now report the production of a uniformly trimeric recombinant HCMV gB protein in Chinese ovary cells, as demonstrated by Western blot analysis under modified non-reducing conditions and size exclusion chromatography with multi-angle scattering. Immunization of mice with trimeric HCMV gB induced up to 11-fold higher serum titers of total gB-specific IgG relative to monomeric HCMV gB using Alum + CpG as adjuvants. Further, trimeric HCMV gB elicited 50-fold higher complement-independent and 20-fold higher complement-dependent HCMV neutralizing titers compared to monomeric HCMV gB using the fibroblast cell line, MRC-5, and up to 6-fold higher complement-independent and –dependent HCMV neutralizing titers using the epithelial cell line, ARPE-19. The markedly enhanced HCMV neutralizing activity in response to trimeric HCMV gB was also observed using an additional four distinct clinical HCMV isolates. These data support a role for trimeric HCMV gB as an important component for clinical testing of a prophylactic HCMV vaccine.